The Impact of excise tariff increases on state revenue - Nugroho, Ario Seno; Riesfandiari, Indri; Ambarwati, Diah Zahi; Pratama, Chandra (Educoretax, 2026)
The Indonesian government implemented an excise tariff increase for Beverages Containing Ethyl Alcohol or alcoholic beverages (MMEA) or in 2024 to mitigate the erosion of real revenue value caused by inflation and to control the consumption of excise goods. This study analyses the economic and fiscal impact of this policy, with a specific focus on revenue realisation at the Banten Regional Customs Office of the Directorate General of Customs and Excise (Kanwil DJBC Banten). Utilising a Computable General Equilibrium (CGE) model processed through GEMPACK software and the 2016 Indonesian Input-Output Table, the research simulates the effects of an 11.81% domestic tariff increase and a 9.8% import tariff increase. The simulation results indicate that the tariff hike moderates the growth of the MMEA industry to 3.4%, trailing the national economic growth baseline of 5.2%. However, despite this industrial deceleration, the policy significantly enhances fiscal performance, with national excise revenue projected to rise by 25.31%. At the regional level, Banten Regional Customs Office is projected to realise a total revenue of IDR 3.2 trillion in 2024, representing a net increase of approximately IDR 600 billion across Class A, B, and C alcoholic beverages compared to the previous year. These findings demonstrate that the 2024 tariff adjustment effectively achieves the dual policy objectives of restricting the expansion of controlled goods while simultaneously optimising state revenue collection. The simulation results indicate that the tariff hike moderates the growth of the MMEA industry to 3.4%, trailing the national economic growth baseline of 5.2%. However, despite this industrial deceleration, the policy significantly enhances fiscal performance, with national excise revenue projected to rise by 25.31%. At the regional level, Banten Regional Customs Office is projected to realise a total revenue of IDR 3.2 trillion in 2024, representing a net increase of approximately IDR 600 billion across Class A, B, and C alcoholic beverages compared to the previous year. These findings demonstrate that the 2024 tariff adjustment effectively achieves the dual policy objectives of restricting the expansion of controlled goods while simultaneously optimising state revenue collection.